2023
DOI: 10.1101/2023.11.30.569494
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Simultaneous CRISPR screening and spatial transcriptomics reveals intracellular, intercellular, and functional transcriptional circuits

Loϊc Binan,
Serwah Danquah,
Vera Valakh
et al.

Abstract: Pooled optical screens have enabled the study of cellular interactions, morphology, or dynamics at massive scale, but have not yet leveraged the power of highly-plexed single-cell resolved transcriptomic readouts to inform molecular pathways. Here, we present Perturb-FISH, which bridges these approaches by combining imaging spatial transcriptomics with parallel optical detection ofin situamplified guide RNAs. We show that Perturb-FISH recovers intracellular effects that are consistent with Perturb-seq results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…In order to achieve both high CRISPR and IVT efficiencies, we designed a chimeric promoter, where the T7 sequence is embedded within the U6 promoter as close as possible to the sgRNA without disrupting CRISPR activity. The published U6/ T7 promoter design 31,32 resulted in substantial decreases in editing efficiency ( Fig. S1c,d ), necessitating the design of a new chimeric promoter to support highly efficient screens.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to achieve both high CRISPR and IVT efficiencies, we designed a chimeric promoter, where the T7 sequence is embedded within the U6 promoter as close as possible to the sgRNA without disrupting CRISPR activity. The published U6/ T7 promoter design 31,32 resulted in substantial decreases in editing efficiency ( Fig. S1c,d ), necessitating the design of a new chimeric promoter to support highly efficient screens.…”
Section: Resultsmentioning
confidence: 99%
“…FISH-based detection of sgRNAs and barcodes has recently emerged as an alternative to ISS for reading out multiplex screens 12,32,54 . These methods generally either directly detect an sgRNA with a FISH probe or detect an expanded FISH barcode often proximal to the sgRNA of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Several more studies have examined ASD risk genes in parallelized in vitro screens, similarly identifying neurogenesis-related phenotypes without clear molecular correlates. Additionally, the in vitro studies chose genes based on manual curation [27][28][29][30][31] , and sometimes even further restricted to those with similar putative biological functions 27,29 . Although manually-curated gene lists tend to be more comprehensive, they also tend to introduce a degree of bias that is largely avoided by focusing on genes identified by exome-and genome-wide approaches (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…They also highlighted several molecular processes as possible points of convergence, though specific processes were not consistently identified across more than one study and the pre-selection of genes reduces the generalizability of these findings. In addition to neural cells, a recent study screened perturbations of 127 manually curated ASD risk genes for disruption of ATP-mediated calcium activity in iPSC-derived astrocytes 31 . Although this study observed functional convergence in that a subset of genes resulted in dysfunctional calcium activity, specific points of molecular convergence were not characterized and the broader relevance of these findings to ASD is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, Feldman et al developed an optical pooled screen that can systematically analyze genetic components and conduct phenotypic analysis with a wide range of spatial and temporal definitions after gene perturbation [ 133 ]. The development of an optical pool screen that can observe dynamic phenotypic changes in cells is exciting [ 134 ].…”
Section: Joint Applications With Other Technologiesmentioning
confidence: 99%